Early introduction of oral paricalcitol in renal transplant recipients. An open‐label randomized study. (2nd June 2017) - Pihlstrøm, Hege Kampen; Gatti, Franscesca; Hammarström, Clara; Eide, Ivar Anders; Kasprzycka, Monika; Wang, Junbai; Haraldsen, Guttorm; Svensson, My Hanna Sofia; Midtvedt, Karsten; Mjøen, Geir; Dahle, Dag Olav; Hartmann, Anders; et al.
Summary: In stable renal transplant recipients with hyperparathyroidism, previous studies have indicated that vitamin D agonist treatment might have anti‐proteinuric effects. Animal studies indicate possible anti‐fibrotic and anti‐inflammatory effects. Early introduction of paricalcitol in de novo renal transplant recipients might reduce proteinuria and prevent progressive allograft fibrosis. We performed a single‐center, prospective, randomized, open‐label trial investigating effects of paricalcitol 2 μg/day added to standard care. Participants were included 8 weeks after engraftment and followed for 44 weeks. Primary end point was change in spot urine albumin/creatinine ratio. Exploratory microarray analyses of kidney biopsies at study end investigated potential effects on gene expression. Secondary end points included change in glomerular filtration rate (GFR), pulse wave velocity (PWV), and endothelial function measured by peripheral arterial tonometry as reactive hyperemia index (RHI). Seventy‐seven de novo transplanted kidney allograft recipients were included, 37 receiving paricalcitol. Paricalcitol treatment lowered PTH levels ( P  = 0.01) but did not significantly reduce albuminuria ( P  = 0.76), change vascular parameters (PWV; P  = 0.98, RHI; P  = 0.33), or influence GFR ( P  = 0.57). Allograft gene expression was not influenced. To summarize, in newly transplanted renal allograft recipients, paricalcitol reduced PTH and was well tolerated without negatively affecting kidney function. Paricalcitol did not significantly reduce/prevent albuminuria, improve parameters of vascular health, or influence allograft gene expression.